Integrated quality assurance frameworks in higher education: Aligning institutional standards with evolving market demands - Renda Lestari; Rahmadani, Mutia; Oktavia, Diana (Institute of Information Technology and Social Science (IITSS), 2026)
This research endeavors to evaluate the efficacy of an integrated quality assurance system in enhancing the quality of education to align with market demands. The 'Unggul' predicate was granted to Padang State University (UNP), which is one of the universities in Indonesia where this study was conducted. Utilizing a qualitative research methodology in phenomenology, data were collected to investigate the implementation of the quality assurance system at UNP, from planning to operation, in order to comprehend its influence on the quality of learning within the university environment. This investigation demonstrated that there is an urgent necessity to enhance the integration of education with the requirements of a job market that is both dynamic and rapidly evolving. While the EPP (Determination, Implementation, Evaluation, Control, and Improvement) model has demonstrated efficacy, technological advancements and global dynamics necessitate additional innovation and adaptation.